LEGAL ANALYSIS OF PAWNBROKING IN FIQH MUAMALAH AND ITS IMPLICATIONS IN ISLAMIC FINANCE PRACTICE - Nurlaela, Nurlaela; Mafaza, Arsya; Andhini, Andhini; Jamilah, Siti; Malik, Muhamad Ibnu (ANAYASA : Journal of Legal Studies, 2026)
Rahn (Sharia pawning) is a crucial instrument for mitigating collateral-based financing risk in Fiqh Muamalah, founded on the principles of ta'awun (mutual help) and justice. This study aims to analyze the normative basis of rahn, compare it with conventional pawning, and critically evaluate the implementation of Rahn Bi Ujrah in Islamic Financial Institutions (LKS) using a normative-comparative literature review approach. The findings indicate that while Rahn Bi Ujrah is jurisprudentially permissible, provided the ujrah (fee) is based on real costs and separated from the loan contract, structural contradictions exist in the practice of Sharia Banks. The determination of ujrah percentages correlating with the loan amount suggests that the fee functions as the price of capital usage, potentially violating the DSN-MUI Fatwa. Conversely, OJK regulations enforce Maqashid Syariah principles during the execution phase, mandating the return of surplus funds from collateral auctions to the customer. The study concludes that stricter regulatory standardization of ujrah is essential to ensure comprehensive compliance and maintain the credibility of the Islamic financial system.